Objective structured clinical examination (OSCE) in pharmacy education - a trend - Shirwaikar A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Pharmacy education has undergone a radical change as it evolves towards becoming a more patient oriented profession. With a greater emphasis on problem based teaching and competency, the Objective Structured Clinical Examination (OSCE), supported by its reliability and validity became the gold standard for the evaluation of clinical skills of undergraduate students of medicine and pharmacy worldwide. Core competency evaluation has become a mandatory and critical norm for accountability of educational objectives as the traditional testing tools cannot evaluate clinical competence. Interpersonal and communication skills, professional judgment, skills of resolution etc., may be best assessed through a well- structured OSCE in comparison to oral examinations, multiple choice tests and other methods of assessment. Though OSCEs as an objective method of evaluation offer several advantages to both students and teachers, it also has disadvantages and pitfalls in implementation. This article reviews the OSCE as a trend in pharmacy education.